The end of Londongrad? The impact of beneficial ownership transparency on offshore investment in UK property - Matthew Collin; Florian M. Hollenbach; David Szakonyi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The United Kingdom's (UK) property markets are thought to be a common destination for corrupt and criminal assets and money laundering, with investment often through offshore shell companies. Following the Russian invasion of Ukraine in 2022, we study the impact of the introduction of a policy in the UK intended to increase transparency and eliminate the anonymous ownership of property by requiring offshore companies to file their ultimate beneficial owners on a public register. We find that new purchases by companies based in tax havens fell substantially following government announcements that the policy would be introduced that year, and further declined following the establishment of a register of ownership. While the policy has effectively led the offshore market to stall, 44-76 billion worth of UK real estate is still owned by companies based in tax havens, most of which have yet to comply with their reporting obligations. We do not find strong evidence of price effects nor substitution into ownership through suspicious domestic companies, although larger movements may manifest as firms react to the finalization of the policy in early 2023.
Keywords: H20; H26; H71; 330; money laundering; real estate; beneficial ownership; transparency; invasion of Ukraine